Transforming Dental Care: Integrating Geriatric Dentistry, Gerodontology, and Digital Marketing in Public Health - Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida; Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida (Digital Marketing for Public Dental Health: Global Impact Strategies, 2027)
The aging of the global population presents a significant challenge to public health, demanding innovative and sustainable dental approaches. This integrative literature review synthesizes research on the intersection of Geriatric Dentistry, Gerodontology, and digital marketing and communication str...

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Association Between Social Determinants of Health and Borderline Personality Disorder: A Systematic Review - Guerrera, Patrick; Sawadogo, Wendemi; Baviskar, Snehal; Pham, Julie; Patel, Nirali; Cyrus, John (Personality and Mental Health, 2025)
Keywords: Association (psychology); Borderline personality disorder; Context (archaeology); Interpersonal relationship; Mental health; Personality; PsycINFO; Social determinants of health; borderline personality disorder; dept.pch; education; income; social determinants of health; social support; socioeconomic status

Determinants of Healthcare Professionals’ Intentions to Use Telemedicine for Elderly Care in Algeria: A Technology Acceptance Model Approach - Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed Chemseddine; Martínez Asanza, Dachel; Evans, Marian A.; Baviskar, Snehal (Geriatrics, 2026)
Background/Objectives: Telemedicine offers significant potential to improve the quality and accessibility of geriatric care, particularly in resource-constrained settings. However, its effective implementation depends largely on healthcare professionals’ acceptance and willingness to use such systems. Drawing on an extended Technology Acceptance Model (TAM), this study examines the determinants of doctors’ and nurses’ intentions to adopt telemedicine for elderly care in Algeria, with particular emphasis on self-efficacy and institutional support. Methods: This cross-sectional study employed a structured questionnaire administered to 130 healthcare professionals, including physicians and nurses, in Algeria. Hierarchical multiple regression analysis was conducted to test the proposed hypotheses and assess the incremental explanatory power of the extended model. Results: The extended TAM accounted for 48.7% of the variance in intention to use telemedicine. Institutional support (β = 0.432, p < 0.001) and self-efficacy (β = 0.264, p = 0.001) emerged as the strongest predictors. Perceived ease of use (β = 0.178, p = 0.038) and perceived usefulness (β = 0.139, p = 0.021) also had significant positive effects. The inclusion of self-efficacy and institutional support increased the model’s explanatory power by 23.5%. Conclusions: The findings highlight the critical role of organizational support mechanisms, digital competencies, and system usability in fostering telemedicine adoption among healthcare professionals. The study provides practical implications for policymakers and healthcare institutions, emphasizing the need for targeted training programs, supportive infrastructure, and institutional policies that enhance confidence and facilitate the integration of telemedicine into clinical workflows.
Keywords: Algeria; Technology Acceptance Model (TAM); cross-sectional study; dept.pch; digital health; elderly care; healthcare professionals; institutional support; self-efficacy; telemedicine